2019
DOI: 10.3390/ijerph16183326
|View full text |Cite
|
Sign up to set email alerts
|

What Has Been the Focus of Sugarcane Research? A Bibliometric Overview

Abstract: Sugarcane is one of the main crops worldwide, and it has an important impact on environmental issues. A bibliometric mapping analysis of the research on sugarcane was carried out, using data on the titles, abstracts, and keywords of articles published in leading journals and other peer-reviewed documents available in the SCOPUS database from 1858 to 2019 (27 August), and this was subsequently analyzed with the software VOSviewer. The three most important countries that publish research and were most-cited rega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 91 publications
(93 reference statements)
0
7
0
1
Order By: Relevance
“…To reduce such a harmful effect, conversion of unwanted sugarcane leaves into value-added products is necessary [ 5 ]. Although a number of studies have shown the promising potential of sugarcane biomass [ [6] , [7] , [8] ], only a few reports have emphasized sugarcane leaves [ [9] , [10] , [11] , [12] , [13] , [14] , [15] ].…”
Section: Introductionmentioning
confidence: 99%
“…To reduce such a harmful effect, conversion of unwanted sugarcane leaves into value-added products is necessary [ 5 ]. Although a number of studies have shown the promising potential of sugarcane biomass [ [6] , [7] , [8] ], only a few reports have emphasized sugarcane leaves [ [9] , [10] , [11] , [12] , [13] , [14] , [15] ].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, a signi cant fraction that is not used continues to impact the environment [10]. The cane residues that are lost during cutting and harvesting (Sugarcane Wastes) vary according to the volume of biomass produced, crop management, and irrigation or temporary system [11]; it is estimated that for every 100 tons of total sugars reached from the eld, 134 tons of agricultural residues are dispersed in the area, affecting the productivity of the sugarcane elds [5].…”
Section: Introductionmentioning
confidence: 99%
“…Por seu turno, o custo de oportunidade assumiu distintos valores segundo diferentes escalas de explorações consideradas: US$/m3 0,01224 para explorações de 15 ha; US$/ m3 0,1056 para explorações de 23 ha; US$/m3 0,1715 para 23 ha com irrigação antes da obra. Palavras-chave: cana-de-açúcar, plantação, função de produção, painel de dados, comando xtlsdv, Colômbia y plagas, mejoras fisiológicas, inmunológicas, labores y técnicas agrícolas, sistemas de riego, el uso de químicos, mestizaje con otras especies y el análisis del genoma se impulsan la maximización, no solo de la producción de caña y su rendimiento por hectárea, sino también de los productos que de esta se derivan (Figueroa-Rodríguez et al, 2019;Núñez, Ruiz, Parra y Ortiz, 2019).…”
Section: Introductionunclassified